Age-related effects of restraint stress on ethanol intake - Wille-bille, Aranza (2017)
Several work has suggested that adolescents may be significantly more sensitive to stress, and to ethanol-stress interactions, than adults. It is thus important to analyze stress-reactive drinking during adolescence and potential treatments to ameliorate it. Stress effects upon ethanol intake in animal rat models have been controversial, with studies indicating heightened, decreased or unaltered ethanol intake after stress. The present study analyzed the impact of chronic restraint stress (5 daily, 2h long, sessions) upon ethanol intake, assessed across two-weeks via intermittent, 18-h two bottle intake tests, in male and female adolescent and adult rats. We found greater ethanol intake and preference in stressed than in non-stressed female, but not in male, adolescent rats. This effect of stress was inhibited after blockade of kappa opioid receptors by norbinaltorphimine (10 mg/kg). Significant age-related differences were observed, with stressed-adult females drinking actually less than their same-age controls. In subsequent experiments we observed that adolescent stressed females exhibited signs of behavioral disinhibition when tested in a modified version of the concentric square field test. Altogether, these results confirm the hypothesis of greater adolescent reactivity to stress, which can result in increased liability for ethanol intake, particularly among females. Treatments that tackle the endogenous opioid system, in particular the kappa receptors, seem to hold promise as a therapeutic target to reduce this stress-mediated ethanol drinking.